Membangun Kemampuan Problem Solving Matematika Berbasis Pola Pikir Logis untuk Persiapan UTBK - Abdurahim, Abdurahim; Salwa, Salwa; Ramadhan, Hikmal Maulana; Choirunnisa, Fajarani; Pradana, Satriawan; Marwan, Marwan; Alfian, Muhammad Rijal; Aini, Qurratul; Robbaniyyah, Nuzla Af'idatur; Awalushaumi, Lailia (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
Mastery of mathematical problem-solving skills based on logical reasoning is an important aspect in supporting students’ success in facing the Computer-Based Written Examination (UTBK). However, many students still encounter difficulties in understanding concepts and effectively solving UTBK-type questions. To address this issue, a community service program was conducted at SMA Negeri 1 Pujut with the aim of enhancing participants’ mathematical reasoning capacity. The activity began with an introduction to the Mathematics study program, followed by training sessions on strengthening concept mastery through logical reasoning and practice in solving UTBK questions, delivered by lecturers and students. The effectiveness of the training was evaluated through a comparison of participants’ pre-test and post-test results. This activity was attended by 30 students as training participants. The evaluation showed a significant improvement in post-test scores, with 83.33% of participants experiencing an increase in their scores, and the majority achieving above 60 in the post-test. These findings indicate that the applied training method was effective in improving students’ conceptual understanding of mathematics and their readiness to face the UTBK.